Student-led development of a lightboard to enhance future student learning. Issue 2 (April 2022) - Swenson, Matthew J; Spence, Taylor; Smentkowski, Brian
Lightboards are emerging technologies, helping to optimize online and flipped classroom environments by enabling the instructor to face the audience while writing on a transparent board. Although both commercial and do-it-yourself designs of lightboards are currently available, we have conducted a student-led engineering research and design project to optimize a lightboard design for broader use on campus to enhance the learning of future students. Through systematic side-by-side comparison, the team determined that Starphire Ultra-Clear™ glass is more appropriate than standard window glass for larger lightboard designs, despite its higher cost. The fully built and validated solution is housed in the campus Library for broad implementation into classroom environments throughout all institution outlets. The effectiveness of the lightboard is evaluated through a student comparison of short online videos generated using three separate formats: narrated slides, whiteboard, and the new lightboard. Students in a hybrid in-person and online class favored having the instructor facing the camera (76%), hand-written content (64%), and the use of more advanced technology (67%). Furthermore, through a pairwise polling comparison, students consistently favored the lightboard over narrated slides or simple whiteboard presentation formats.